Contemporary textile sculpture - Schneder, A. (Theory and practice of design, 2016)
The article observes the emergence and establishment of the textile sculpture. Ascertain that the first attempts to create it were made in the 30-s of the XX century. These attempts were made by the surrealist artists. Types of textile sculpture and its main forms were analysed. The place and the role of contemporary spatial forms оf textile art and design were determined. The usage of materials, techniques and technologies, depending on types and purposes of textile objects, was researched. The analysis of basic forms and types of contemporary textile sculpture was made. A significant role of sculptors and painters of the 50-60-s of the XX century, who have chosen textile as a material for execution of their creative works, has been ascertain in the further development of textile sculpture as a form of modern art. Plastic qualities of the materials as well as techniques and technologies and their impact on plastic and form of spatial textile were examined. The interaction of materials, techniques and concepts were researched as well as their compositional solutions, which define aesthetic, emotional and other qualities of textile sculpture.